Pemberdayaan Komite Sekolah dalam Meningkatkan Mutu Pendidikan di Sekolah Dasar Negeri Kecamatan Syiah Kuala Banda Aceh - Sakdiah Sakdiah; Zamzami Zamzami (Center for Research and Community Service (LPPM) University of Abulyatama, 2018)
The problems of school-based management in terms of improving the quality of education that has not been solved at this time is one of them related to the empowerment of the school committee. Ideally the school committee should be a parallel partner for the principal and teachers in adopting policies for improving the quality of education. The purpose of this study was to determine the empowerment of school committees in improving the quality of education at Syiah Kuala State Elementary School in Banda Aceh. The method used in this research is descriptive method with qualitative approach. Technique research data of this research is interview, observation, and documentation. The subjects of this research are principals, school committees, and teachers of Syiah Kuala State elementary school in Banda Aceh. The conclusion of the research shows that the effort done by the school in empowering the school committee is to make regular meetings every three months, and to make a meeting at the end of each semester. It was at this meeting that the principal and the school committee discussed important matters concerning improving the quality of education quality improvement and other matters deemed necessary. The involvement of school committees in formulating work programs generally can be said to run well. In every work program preparation, the school always involves school committees and teachers so that each work program is really known by the school committee. The authority of the school committee is not the same as the principal, including in managing school finances. School committees have limited authority to provide certain inputs or considerations regarding school programs. Thus, the authority of the school committee is not yet optimal, especially in financial management..